2010
DOI: 10.1088/0004-637x/718/2/620
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Period and Outburst Luminosity of Transient Low Mass X-Ray Binaries

Abstract: In this paper we investigate the relation between the maximal luminosity of X-ray outburst and the orbital period in transient low mass X-ray binaries (or soft X-ray transients) observed by the Rossi X-ray Timing Explorer (RXTE) in the past decade. We find that the maximal luminosity (3-200 keV) in Eddington unit generally increases with increasing orbital period, which does not show a luminosity saturation but in general agrees with theoretical prediction. The peak luminosities in ultra-compact binaries might… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 75 publications
12
69
3
Order By: Relevance
“…Finally, the maximum luminosity that can be reached during outburst should scale with the orbital period of the binary (e.g., Lasota 2001), which is borne out by observations (e.g., Wu et al 2010). For the estimated bolometric peak X-ray luminosity of RXS J1804 (L bol ≃5 × 10 37 erg s −1 ), the empirical relation of Wu et al (2010) yields an orbital period of ≃1.4 hr.…”
Section: On the Size Of The Binary Orbitmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, the maximum luminosity that can be reached during outburst should scale with the orbital period of the binary (e.g., Lasota 2001), which is borne out by observations (e.g., Wu et al 2010). For the estimated bolometric peak X-ray luminosity of RXS J1804 (L bol ≃5 × 10 37 erg s −1 ), the empirical relation of Wu et al (2010) yields an orbital period of ≃1.4 hr.…”
Section: On the Size Of The Binary Orbitmentioning
confidence: 97%
“…For the estimated bolometric peak X-ray luminosity of RXS J1804 (L bol ≃5 × 10 37 erg s −1 ), the empirical relation of Wu et al (2010) yields an orbital period of ≃1.4 hr. Disk instability theory predicts an orbital period of ≃2.4 hr for an irradiated He disk .…”
Section: On the Size Of The Binary Orbitmentioning
confidence: 99%
“…These populations of extra-galactic LMXBs provide a wider observational base for the understanding of LMXB formation and evolution, which has been debated since their discovery in the Milky Way (see, e.g., Giacconi 1974;Grindlay & Henz 1985; review by Verbunt & van den Heuvel 1995;Piro & Bildsten 2002;King 2002;Bildsten & Deloye 2004). A key observational result that can constrain the nature of these LMXBs is their time variability, as luminous LMXBs (L X 10 37 erg s −1 ) in relatively wide orbits are expected to exhibit transient behavior, according to the "standard" formation scenario of LMXBs in galactic fields (Verbunt & van den Heuvel 1995;Shahbaz et al 1997;Piro & Bildsten 2002;King 2002;Wu et al 2010). For sources originating as ultracompact binaries formed in globular clusters (GCs) instead, transient behavior is only expected at lower luminosities (Bildsten & Deloye 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Wu et al (2010) found that 3−200 keV peak luminosity of XTE J1118+480 is only about 0.001 L Edd , which implied a low mass transfer rate of …”
Section: Magnetic Brakingmentioning
confidence: 99%